Analisis Instrumen Tes Kemampuan Berpikir Kritis Siswa Pada Pembelajaran Matematika Materi Barisan dan Deret - Nada, Nabillah Qatrun; Yulia, Putri (Malewa: Journal of Multidisciplinary Educational Research, 2023)
This study aims to analyze students' critical thinking skills in learning mathematics, especially the matter of sequences and series in class XI MIA 4 MA Negeri 1 Sungaipuh City. The method used in this study was the Chroschek sectional survey, the sample in the study was determined using simple random sampling, in which the researcher took the sample randomly to obtain Class XI MIA 4 consisting of 32 students. Data collection techniques in the form of tests. The test instrument in this study was a description item consisting of 3 items to measure students' critical thinking skills. Each item contains 5 indicators of critical thinking skills, including interpretation, analysis, explanation, evaluation and inference. Based on the results of the analysis, it was found that the critical thinking skills of students in class XI MIA 4 MAN 1 Sungai Full City in the material for sequences and series were still lacking with an average value of 40.8. Students' critical thinking skills appear the most in analytical indicators. The lack of students' ability is influenced by various factors, namely, the lack of mindset in solving problems and understanding concepts. Thus, the teacher plays an important role in developing students' mathematical critical thinking skills